1 PENGAWASAN PENATAAN PEDAGANG KAKI LIMA DI SIMPANG LIMA SEMARANG - Adimas Bagus Pamungkas; Ari Subowo; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
The existence of street vendors are often cause a dilemma in every region, on one hand can increase local income. But, on the other hand can reduce the beauty of the city and causing jams. In Indonesia, especially Semarang, Government has made a Regional Regulation Number 11 years 2000 about Setting and Development of Street Vendors to resolve the existing problems of street vendors in Semarang. On the implementation, the government's control to the street vendors who have been set is very lack.The purpose of research is to describe the process of Controlling Structuring The Street Vendors that exists around Simpang Lima Semarang. The theory that used in this research is controlling process using variable of standard setting, monitoring, evaluation, and corrective action. This research use descriptive qualitative methods, and the informant is from Markets Departement and streetvendors around Simpang Lima Semarang.Overall results of this research is, controlling structuring of street vendors in Simpang Lima Semarang is still ineffective. The main problem that cause the lack of effective controlling is insufficient availability of human resources. Minimal amount of human resources will affect to the intensity of controlling.